Strategic policing philosophy and the acquisition of technology: findings from a nationally representative survey of law enforcement. (24th July 2019) - Hendrix, Joshua A.; Taniguchi, Travis; Strom, Kevin J.; Aagaard, Brian; Johnson, Nicole
ABSTRACT: Police departments that emphasise certain strategic models (e.g. community-oriented policing, problem-oriented policing) may adopt specific types of technology to better achieve their core missions. A contrasting theory is that police agencies do not invest strategically in technology; rather, they adopt technology in a 'black box' without a larger plan for how a particular technology fits within the agency's guiding philosophy or operational goals. Despite the importance of this discourse, very little research has been conducted to address these claims. Using survey data from a large and nationally representative sample of police agencies in the United States ( N = 749), we examine whether strategic police goals are associated with technology use for six core technologies (crime mapping, social media, data mining software, car cameras, license plate readers (LPRs), and body-worn cameras (BWCs)). Nationally, across the sample of all US law enforcement agencies, we find little relationship between strategic goals and technology. Agency size, rather than policing philosophy was a more important determinant of technology use. However, stronger relationships between strategy and technology emerged when the analysis was limited to a subsample of larger agencies (250 or more sworn officers). Specifically, community and hot spot policing strategies were positively associated with the use of geographic information system technology, social media, and LPRs. Agencies who emphasised hot spot policing were also more likely to have used BWCs. Implications of these findings are discussed.